2009
DOI: 10.1097/opx.0b013e3181ae1b7c
|View full text |Cite
|
Sign up to set email alerts
|

Visual Discomfort and Objective Measures of Static Accommodation

Abstract: Accommodative insufficiency and fatigue should be defined and described by objective methods using extended viewing times to assess function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 31 publications
5
71
0
Order By: Relevance
“…Several studies have found an effect of pattern glare/visual discomfort on accommodation (Allen et al, 2008;Chase et al, 2009;Tosha et al, 2009). Individuals who experience discomfort tend to have a greater lag of accommodation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found an effect of pattern glare/visual discomfort on accommodation (Allen et al, 2008;Chase et al, 2009;Tosha et al, 2009). Individuals who experience discomfort tend to have a greater lag of accommodation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Chase et al (2009) found a positive correlation between the accommodative lag in response to a 0.2m target and the visual discomfort scores from the Conlon Visual Discomfort Survey. Tosha et al (2009) also found that a group which reported high discomfort showed greater fatigue when sustaining accommodation at near distance (3-4D), even over a short time period (90s).…”
Section: Introductionmentioning
confidence: 99%
“…33 Accommodative insufficiency is known to lead to fatigue when reading; however, Chase et al 34 have shown that the common push-up measure of accommodation overestimates accommodative performance. A strong and positive correlation between accommodative lag and visual discomfort symptoms was found under near-work conditions by Chase et al 34 and they concluded that the prevalence of accommodative insufficiency was much higher than estimated by clinical measures when an open field autorefractor was used to assess accommodative lag. Others 35 have aso shown that accommodative lag increases more quickly in visually symptomatic readers, making blur more likely.…”
Section: Accommodative Lag and Visual Discomfortmentioning
confidence: 99%
“…These factors are divided into the following two main categories: differences between retinal images [4][5][6][7][8][9], and mismatch between accommodation and convergence [10][11][12][13][14][15]. The experiment was conducted by using two different groups of participants: movies original3D and altered3D were compared in one group (referred to as the original3D-altered3D group), and movies 2D and altered3D were compared in the other group (referred to as the 2D-altered3D group).…”
Section: Introductionmentioning
confidence: 99%